Perception of Consumers towards Nepalese Insurance Products - Adhikari, Pitri Raj (Journal of Nepalese Business Studies, 2020)
This paper examines the changing perception of consumers towards Nepalese insurance products. Descriptive and causal-comparative research designs are used to achieve the objectives and data are collected through a structured questionnaire from 400 respondents of Kathmandu valley and Parsa district. Descriptive statistics, as well as multiple regression models, are used to analyze the data. It is found that consumer perception (dependent variable) is positively correlated with independent variables (company loyalty, service quality, satisfaction level, company image and ease of procedures). Company image, company loyalty and satisfaction level are the most dominant factors that influence the perception of consumers towards insurance products in the context of Nepalese insurance companies. This study is an endeavor to extend the literature of changing the perception of consumers towards insurance products and it is the first to report the evidence from the combination of Kathmandu valley and Birgunj metropolitan city of Parsa district perspective.